A tradução de contratos de distribuição no par de línguas inglês-português: uma análise funcionalista e terminológica - Costa, José Helder de Lima (2018)
Within the field of specialized communication, Translation Studies are closely linked to the progress of language and cultural manifestation. Therefore, the required knowledge of the translator goes beyond the linguistic domain, especially when the translation purpose is to produce a target text suitable to the target audience’s cultural reality. Based on this finding, our research aims at evaluating the translation practice through a sequential model of text analysis of English-to-Portuguese distribution agreement translation by applying Functionalist Approach (REISS, VERMEER, 1996; NORD, 2012, 2016) and Terminology (CABRÉ, 2004; KRIEGER; FINATTO, 2004). Specifically, we aimed to verify whether translators, regardless of their professional training and practice used, even if intuitively, the analytical model (NORD, 2016) to investigate whether it would be possible to make critical analysis of translation choices based on functionalism with a terminological approach; and propose a theoretical framework to aid professional translators with their practice. To achieve the said objectives, we made the following methodological steps: analysis and comparison of the extratextual and intratextual factors of four distribution agreements and their respective translations in light of the Functionalist Approach; translation criticism through the translation choices analysis of terms and phraseological units that were recurrent in at least two of the four translated contracts, confronting such choices with their equivalent terminological definitions based on the translation purpose. During our analysis, we could verify the existence of common law legal systems particularities, such as the existence of clauses defining specific terms in the original contracts; we also noted that many translation choices were based on strict observance of gender and textual conventions, such as the preservation of the original term “artigo” as a literal translation of article, rather than a “cláusula”. On the other hand, during the terminological analysis, we observed that the translators possessed a linguistic domain and knowledge about the lexical variations in bilingual terminology, and were aware of the extra and intratextual factors, such as the audience, the place, the presuppositions, the lexicon, and the syntax, since their translations fit into the target public, as required by the translation purpose, when adaptations of the target text to the cultural reality of the target audience were required, for example, the translation of company as “empresa”, rather than “sociedadecomercial”; or the translation of inventory as “estoque”, rather than “inventário”.